Analysis of the CPZ/Wnt4 osteogenic pathway for high-bonding-strength composite-coated magnesium scaffolds through transcriptomics - Zewen Shi; Fang Yang; Tianyu Du; Qian Pang; Chen Liu; Yiwei Hu; Weilai Zhu; Xianjun Chen; Zeming Chen; Baiyang Song; Xueqiang Yu; Zhewei Ye; et al. (Materials Today Bio)
Magnesium (Mg)-based scaffolds are garnering increasing attention as bone repair materials owing to their biodegradability and mechanical resemblance to natural bone. Their effectiveness can be augmented by incorporating surface coatings to meet clinical needs. However, the limited bonding strength and unclear mechanisms of these coatings have impeded the clinical utility of scaffolds. To address these issues, this study introduces a composite coating of high-bonding-strength polydopamine-microarc oxidation (PDA-MHA) on Mg-based scaffolds. The results showed that the PDA-MHA coating achieved a bonding strength of 40.56 ± 1.426 MPa with the Mg scaffold surface, effectively enhancing hydrophilicity and controlling degradation rates. Furthermore, the scaffold facilitated bone regeneration by influencing osteogenic markers such as RUNX-2, OPN, OCN, and VEGF. Transcriptomic analyses further demonstrated that the PDA-MHA/Mg scaffold upregulated carboxypeptidase Z expression and activated the Wnt-4/β-catenin signaling pathway, thereby promoting bone regeneration. Overall, this study demonstrated that PDA can synergistically enhance bone repair with Mg scaffold, broadening the application scenarios of Mg and PDA in the field of biomaterials. Moreover, this study provides a theoretical underpinning for the application and clinical translation of Mg-based scaffolds in bone tissue engineering endeavors.